Key Players and Individualists of Cyclic-di-GMP Signaling in Burkholderia cenocepacia - Richter, Anja M.; Fazli, Mustafa; Schmid, Nadine; Shilling, Rebecca; Suppiger, Angela; Givskov, Michael; Eberl, Leo; Tolker-Nielsen, Tim (Frontiers in Microbiology, 2019)
Burkholderia cenocepacia H111 is an opportunistic pathogen associated with chronic lung infections in cystic fibrosis patients. Biofilm formation, motility and virulence of B. cenocepacia are regulated by the second messenger cyclic di-guanosine monophosphate (c-di-GMP). In the present study we analyzed the role of all 25 putative c-di-GMP metabolizing proteins of B. cenocepacia H111 with respect to motility, colony morphology, pellicle formation, biofilm formation, and virulence. We found that RpfR is a key regulator of c-di-GMP signaling in B. cenocepacia, affecting a broad spectrum of phenotypes under various environmental conditions. In addition, we identified Bcal2449 as a regulator of B. cenocepacia virulence in Galleria mellonella larvae. While Bcal2449 consists of protein domains that may catalyze both c-di-GMP synthesis and degradation, only the latter was essential for larvae killing, suggesting that a decreased c-di-GMP level mediated by the Bcal2449 protein is required for virulence of B. cenocepacia. Finally, our work suggests that some individual proteins play a role in regulating exclusively motility (CdpA), biofilm formation (Bcam1160) or both (Bcam2836).